2015
DOI: 10.1364/ol.41.000119
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental demonstration of a wavelength demultiplexer design by point-defect cavity coupled to a tapered photonic crystal waveguide

Abstract: We propose and experimentally demonstrate a demultiplexer with point-defect resonators and a reflection feedback mechanism in a photonic crystal waveguide (PCW). A tapered PCW has been chosen as the necessary reflector, which enhances the drop efficiency. Due to the variation of the single-mode waveguide width of the tapered PCW, spatial alteration of the effective refractive index can be achieved. This phenomenon is used to reflect back the forward propagating wave which is then coupled again to the drop chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…As a result, it has been found that the termination of the photonic crystal structure can be designed to provide desired surface wave dispersion properties, while an additional corrugation can undertake the coupling of the dark surface states to outgoing radiation. The mechanism has been employed, among others, to sustain the collimation of free-space traveling beams, , to produce and control near-field focusing effects, , and to decrease the π angular spread, or 2π for a solid angle in 3D, of a forward-propagating beam that exits a subwavelength photonic crystal waveguide operating in the microwave and optical regime. Moreover, in the case of the microwave regime and the corresponding high dielectric rods in air photonic crystals, it has been shown both theoretically and experimentally that the angle of the beam’s directionality can be tuned by properly designing the terminating corrugations. , The frequency-dependent bend of the beams provides steering and frequency splitting capabilities, and consequently the manipulation of the dielectric, ohmic-loss-free, surface waves may be used in a variety of applications involving free-space coupling, as for example in demultiplexer components for optical communications, optical spectroscopy, and sensor applications. …”
Section: Dielectric Dark State Manipulationmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, it has been found that the termination of the photonic crystal structure can be designed to provide desired surface wave dispersion properties, while an additional corrugation can undertake the coupling of the dark surface states to outgoing radiation. The mechanism has been employed, among others, to sustain the collimation of free-space traveling beams, , to produce and control near-field focusing effects, , and to decrease the π angular spread, or 2π for a solid angle in 3D, of a forward-propagating beam that exits a subwavelength photonic crystal waveguide operating in the microwave and optical regime. Moreover, in the case of the microwave regime and the corresponding high dielectric rods in air photonic crystals, it has been shown both theoretically and experimentally that the angle of the beam’s directionality can be tuned by properly designing the terminating corrugations. , The frequency-dependent bend of the beams provides steering and frequency splitting capabilities, and consequently the manipulation of the dielectric, ohmic-loss-free, surface waves may be used in a variety of applications involving free-space coupling, as for example in demultiplexer components for optical communications, optical spectroscopy, and sensor applications. …”
Section: Dielectric Dark State Manipulationmentioning
confidence: 99%
“… 27 , 28 The frequency-dependent bend of the beams provides steering and frequency splitting capabilities, and consequently the manipulation of the dielectric, ohmic-loss-free, surface waves may be used in a variety of applications involving free-space coupling, as for example in demultiplexer components for optical communications, optical spectroscopy, and sensor applications. 29 32 …”
mentioning
confidence: 99%
“…By contrast, conveying different wavelengths to specific waveguides can be considered a great opportunity to redesign new compact and efficient optical communication systems. In this direction, in recent decades, WDMs have attracted significant attention with state-of-the-art nanophotonic design tools and approaches [5][6][7][8][9][10][11][12][13][14] . Optically conveying a light source with minimum loss is crucial in the design of efficient and integrable WDMs.…”
Section: Introductionmentioning
confidence: 99%
“…The first method is a conventional educated intuition-based approach. With this method, the designers need to practice their skills regarding a parameter search and analytical formulation or incorporate search algorithms to reach the targeted device [5][6][7][8][9][10][19][20][21][22][23][24][25][26][27][28][29] . By contrast, the second approach is based on advanced algorithms and combined simulations to seek a solution that minimizes (or maximizes) a single objective or multi-objective related to the desired nanophotonics functionalities, also known as an "Inverse Design."…”
Section: Introductionmentioning
confidence: 99%
“…The cut-off frequency variation of these segments provides spatial confinement for the target frequencies, which can be then guided through drop channels. The second structure (DEMUX-2) [15] consists of a PC waveguide with a continuously changing waveguide width, which results in light trapping and reflection at particular positions. Furthermore, the adiabatically tapered waveguide is accompanied by side-coupled PC cavities which are responsible for light extraction from both the incoming signal and reflected signal.…”
Section: Introductionmentioning
confidence: 99%